DENTIGEROUS CYST ASSOCIATED WITH IMPACTED ANTERIOR MAXILLARY (KISTA DENTIGEROUS TERKAIT DENGAN IMPAKSI GIGI ANTERIOR RAHANG ATAS) - Florence Meliawaty (Fakultas Kedokteran Gigi Unjani, 2022)
Dentigerous cysts arise from the dental follicle of unerupted teeth and are cysts of the epithelial lining of the jaws. These cysts and unerupted teeth are frequently discovered during routine radiography examinations. Dentigerous cysts are usually asymptomatic unless the cyst grows large enough to cause swelling. Most dentigerous cysts are common in association with third molars and maxillary canines. Clinical, radiological, and histopathologic findings are used to make a diagnosis. We report a case of a dentigerous cyst associated with two impacted anterior maxillary teeth. The care of a dentigerous cyst in the upper left canine region with lateral incisor and canine impaction is described in this case report. The patient was treated surgically by enucleation of the cyst under general anaesthesia. The healing was good two weeks after surgery, according to the examination. DOI : 10.54052/jhds.sd22.p145-151